Estimating Copper, Manganese and Zinc Micronutrients in Fungicide Applications - Bee Ling Poh; Amanda Gevens; Eric Simonne; Crystal Snodgrass (EDIS)
HS1159, an 8-page fact sheet by Bee Ling Poh, Amanda Gevens, Eric Simonne, and Crystal Snodgrass, uses tomato as an example to list common sources of micronutrients in common fungicides, estimates micronutrient applications for an entire crop, and discusses the availability of these micronutrients so that the contributions of these sources of micronutrients can be factored into the fertilizer programs for vegetable crops. Includes references. Published by the UF Department of Horticultural Sciences, August 2009.